An Implementation of Restorative Justice in Handling Cases of the Beatings Crime - Ahmad Ali Ustadi; Amin Purnawan; Siti Ummu Adillah (Law Development Journal, 2022)
The purpose of this research is to find out and analyze the implementation of restorative justice in handling cases of beatings. To find out and analyze the obstacles that arise in the implementation of restorative justice in handling cases of criminal acts of beatings and their solutions. The method used was a juridical empirical legal approach and the specifications in this study were descriptive analytical. The sources and types of data in this study were secondary data obtained from library studies. The data were analyzed qualitatively. Based on the results of the research that the Implementation of Restorative Justice in Handling Cases of the Crime of Beating is repairing social damage caused by perpetrators, developing remedies for victims and the community, and returning perpetrators to society. This effort requires the cooperation of all parties and law enforcement officials. Obstacles that arise: Lack of community or environmental participation in finding a solution to a case so that they immediately report it to the police; The case handled by the police has been sent SPDP (Notice of Commencement of Investigation) to the District Attorney. The existence of a third party interest in resolving a case at the investigation level, Efforts to overcome Emerging Constraints: Entering cases that have been resolved by the community into the media with twisted words or asking the police leadership (Kapolda, Kapolres) either through the media as well as letters or communication tools.